Autoimmune Pancreatitis. Issue 9 (September 2015) - Chintanaboina, Jayakrishna; Yang, Zhaohai; Mathew, Abraham
<x xml:space="preserve">Abstract</x> Abstract Autoimmune pancreatitis (AIP) is a rare cause of chronic pancreatitis that poses a diagnostic challenge to the clinician in that it mimics pancreatic cancer and presents with painless obstructive jaundice. In this review, we discuss the two types of AIP: type 1, known as lymphoplasmacytic sclerosing pancreatitis and type 2, known as idiopathic duct centric pancreatitis. Type 1 AIP is considered as a pancreatic manifestation of immunoglobulin G4-related disease. The etiopathogenesis of AIP, particularly type 2 AIP, is largely unknown. Both types of AIP have unique pancreatic histological features; however, the radiological and clinical features may mimic those of pancreatic cancer. The most commonly used diagnostic criteria, including the Japan Pancreas Society criteria, the Mayo Clinic HISORt (histology, imaging serology, other organ involvement, and response to therapy) criteria, and the International Association of Pancreatology's international consensus diagnostic criteria, that help to differentiate AIP from pancreatic cancer are reviewed in this article. The treatment of choice for induction of remission for AIP is steroid therapy. Relapses are more common in type 1 AIP. In selected patients, immunomodulators such as azathioprine and rituximab are used to maintain remission.